Vapor-liquid equilibria of the binary system 1-pentanol + anisole and the quaternary system benzene + cyclohexane + 1-pentanol + anisole at 101.32 kPa - Orge, Beatriz (2004)
Vapor-liquid equilibrium (VLE) at 101.32 kPa has been measured for the quaternary system benzene + cyclohexane + 1-pentanol + anisole in an isobaric equilibrium still with secondary recirculation of vapor and liquid phases covering a wide range of concentration. Accurate prediction of activity coefficients and the equilibrium compositions with the UNIFAC group contribution model were obtained with low standard deviations of vapor mole fraction and equilibrium temperatures. The consistency of the measured VLE data were tested with the McDermott and Ellis method.